Prospective nationwide outcome audit of surgery for suspected acute appendicitis. Issue 1 (28th October 2015) - van Rossem, C C; Bolmers, M D M; Schreinemacher, M H F; van Geloven, A A W; Bemelman, W A; Acker, G J D; Akkermans, B; Akkersdijk, G J M; Algie, G D; Allema, J H; Andeweg, C S; Appeldorn, N; et al.
Abstract: Background: Studies comparing laparoscopic and open appendicectomy are difficult to interpret owing to several types of bias, and the results often seem of limited clinical importance. National audits can be valuable to provide insight into outcomes following appendicectomy at a population level. Methods: A prospective, observational, resident-led, nationwide audit was carried out over a period of 2 months, including all consecutive adult patients who had surgery for suspected acute appendicitis. Complications after laparoscopic and open appendicectomy were compared by means of logistic regression analysis; subgroup analyses were performed for patients with complicated appendicitis. Results: A total of 1975 patients were included from 62 participating Dutch hospitals. A normal appendix was seen in 3·3 per cent of patients. Appendicectomy was performed for acute appendicitis in 1378 patients, who were analysed. All but three patients underwent preoperative imaging. Laparoscopy was used in 79·5 per cent of patients; the conversion rate was 3·4 per cent. A histologically normal appendix was found in 2·2 per cent. Superficial surgical-site infection was less common in the laparoscopic group (odds ratio 0·25, 95 per cent c.i. 0·14 to 0·44; P < 0·001). The rate of intra-abdominal abscess formation was not significantly different following laparoscopic or open surgery (odds ratio 1·71, 0·80 to 3·63; P = 0·166). Similar findings were observed in patients with complicated appendicitis. Conclusion: Management of acute appendicitis in the Netherlands is preferably performed laparoscopically, characterized by a low conversion rate. Fewer superficial surgical-site infections occurred with laparoscopy, although the rate of abscess formation was no different from that following open surgery. A low normal appendix rate is the presumed effect of a mandatory preoperative imaging strategy. Abstract : Dutch snapshot of appendicitis care